Customs/Excise Threats and Risk Analysis of Illegal Delivery Services Business Phenomenon in Indonesia - Aldila Kun Satriya; Muhammad Syaroni Rofii (Budapest International Research and Critics University, 2022)
The phenomenon of the development of the Personal Shopper business, most commonly known as Jastip (service delivery) in addition to having a positive impact on the economy for service providers, also poses a negative threat in the context of customs and excise. Violation of the service provider when passing through the entrance to Indonesia risks the loss of state revenue from import duties and taxes in the context of imports as well as the entry of dangerous goods in the form of prohibited or restricted goods. Using a qualitative approach, this article describes the threats and risks of Personal Shopper providers who do not report their luggage to avoid import duty levies. The data analyzed are documents from the Directorate General of Customs and Excise (DJBC) and related theoretical studies. The results showed that illegal “Jastip” had two main threats, namely the threat of violating the procedures for bringing goods/products into Indonesia and the threat of bringing prohibit and restricted goods/products (Lartas). All of these threats pose a risk to the decline in state revenues, the risk of damage to trade and industrial competition and the protection of the public/consumers. A solution is needed from the point of view of the strategic intelligence function within the organization of the Directorate General of Customs and Excise in dealing with threats and risks related to the “Jastip” practice.